Model Prediksi Kinerja Karyawan Berdasarkan Beban Kerja Stres Kerja, dan Kepuasan Kerja - Nurainunnisa , Nurainunnisa; Muh. Akob; Pattarapanna, Pattarapanna; Tafsir, Muhammad (Al-Buhuts, 2024)
This study aims to test and analyze the direct influence of workload, work stress and job satisfaction variables on employee performance and the indirect influence of workload and work stress variables on employee performance with job satisfaction as a mediator at PT Midi Utama Indonesia Tbk. Data collection uses primary data obtained from questionnaires using purposive sampling. The population in this study was 104 respondents. The results of the questionnaire have been tested for validity and reliability using the PLS model scheme and model evaluation, inner model evaluation with determinant coefficient test, model goodness of fit test and hypothesis test both directly and indirectly. The results of this data processing use SmartPLS version 3. The results of the study directly show that the workload variable has a negative and significant effect on employee performance and job satisfaction, the work stress variable does not affect employee performance and job satisfaction, and the job satisfaction variable has a positive and significant effect on employee performance. The results of the study indirectly show that job satisfaction is successful in mediating between workload and employee performance with a significant negative relationship direction, but job satisfaction cannot mediate the effect of work stress on employee performance.